2016
DOI: 10.1055/s-0035-1561852
|View full text |Cite
|
Sign up to set email alerts
|

Reaction between 4-Nitro-1,3-diarylbutan-1-ones and Ammonium Acetate in the Presence of Morpholine and Sulfur: An Efficient Synthesis of 2,4-Diarylpyrroles

Abstract: An efficient synthesis of 2,4-diarylpyrroles is described.Heating a mixture of a 4-nitro-1,3-diarylbutan-1-one and ammonium acetate in the presence of morpholine and sulfur afforded the corresponding 2,4-diarylpyrroles in excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…In continuation of our endeavours towards the synthesis of biologically active organic compounds from readily accessible precursors, in this work we sought to explore an efficient four‐component synthesis of functionalized thiophenes from 1,3‐dicarbonyl compounds, aldehydes, activated methylene halides and elemental sulfur (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of our endeavours towards the synthesis of biologically active organic compounds from readily accessible precursors, in this work we sought to explore an efficient four‐component synthesis of functionalized thiophenes from 1,3‐dicarbonyl compounds, aldehydes, activated methylene halides and elemental sulfur (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Added to a solution of 1 mmol of substituted phenacyl bromide (78) were 1 mmol substituted amino unsaturated ketone (79) and 10 mol% of BF 3 OEt 3 in dichloromethane and the mixture was irradiated with MWs for 10-16 min at 130°C (250 W). Adib et al [27] showed the reaction of 4-nitro-1, 3-diarylbutan-1-ones (81) and ammonium acetate (82) in the presence of morpholine and sulphur provides the corresponding 2, 4-diarylpyrroles (83) in excellent yields. Morpholine is used to create all volatile environment and also due to its slow decomposition at high temperatures and pressures.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [12] synthesized 2, 4-and 2, 3, 4-substituted pyrroles (27) in two or three steps from commercially available ketones (26) and allyl hydroxylamine. An iridium-catalyzed isomerization reaction was developed to convert o-allyl oximes to o-vinyl oximes, which undergo a facile [3,3] rearrangement to form 1, 4-imino aldehyde Paal-Knorr intermediates that cyclized to afford the corresponding pyrroles.…”
Section: Methodsmentioning
confidence: 99%
“…In 2016 Adib et al . reported a method of synthesis of 2,4‐diphenylpyrrole ( 6 ) that involved the reaction of 4‐nitro‐1,3‐diarylbutan‐1‐one with ammonium acetate in the presence of morpholine and elemental sulfur.…”
Section: Figurementioning
confidence: 99%